Bennett's War [videorecording (DVD)] - Roark, Michael; Adkins, Trace; Afshar, Ali; Paige, Allison, 1989- (Warner Bros., 2019)
Marshall Bennett is a young soldier with the Army Motorcycle Unit who survives an IED explosion in combat overseas, and is medically discharged with a broken back and leg and sent back to the U.S. When he gets home to his family farm, he discovers that his dad, Cal, is behind in the mortgage and may lose the farm. Against all odds, Marshall pledges to help his family by the only means he knows how, as a motocross racer.